The impact of operational risks according to Basel II Committee requirements on the financial performance of Libyan commercial banks - سالم عبد الكافي, أشرف (Dirasat in Economics and Business, 2024)
This study aimed to investigate the impact of operational risks according to Basel II Represented by (implementation and operations administration, employees, automatic systems), requirements on the financial performance of Libyan commercial banks. To achieve the study's objective, a questionnaire was designed to collect data from a sample of commercial banks operating in the municipality of Sirte, Libya. The collected data was analyzed using the Statistical Package for the Social Sciences (SPSS) software, which involved analyzing 103 valid questionnaires. The hypotheses were tested using various statistical methods, including mean, standard deviation, relative weight, relative importance, Pearson correlation coefficient, and multiple regression analysis. The study found a moderate positive correlation between the independent variables (execution and operations management, employees, automated systems) and the financial performance of banks. Additionally, there was a statistically significant impact of execution and operations management, as well as automated systems, on the financial performance of Libyan commercial banks. However, the variable of employees had no impact on financial performance, despite a positive correlation being present.